Under the Radar: Epidemiology of Plasmodium ovale in the Democratic Republic of the Congo. (7th August 2020) - Mitchell, Cedar L; Brazeau, Nicholas F; Keeler, Corinna; Mwandagalirwa, Melchior Kashamuka; Tshefu, Antoinette K; Juliano, Jonathan J; Meshnick, Steven R
Abstract: Background: Plasmodium ovale is an understudied malaria species prevalent throughout much of sub-Saharan Africa. Little is known about the distribution of ovale malaria and risk factors for infection in areas of high malaria endemicity. Methods: Using the 2013 Democratic Republic of the Congo (DRC) Demographic and Health Survey, we conducted a risk factor analysis for P. ovale infections. We evaluated geographic clustering of infections and speciated to P. ovale curtisi and P. ovale wallikeri through deep sequencing. Results: Of 18 149 adults tested, we detected 143 prevalent P. ovale infections (prevalence estimate 0.8%; 95% confidence interval [CI], .59%–.98%). Prevalence ratios (PR) for significant risk factors were: male sex PR = 2.12 (95% CI, 1.38–3.26), coprevalent P. falciparum PR = 3.52 (95% CI, 2.06–5.99), and rural residence PR = 2.19 (95% CI, 1.31–3.66). P. ovale was broadly distributed throughout the DRC; an elevated cluster of infections was detected in the south-central region. Speciation revealed P. ovale curtisi and P. ovale wallikeri circulating throughout the country. Conclusions: P. ovale persists broadly in the DRC, a high malaria burden country. For successful elimination of all malaria species, P. ovale needs to be on the radar of malaria control programs. Abstract : Plasmodium ovale is present and broadly distributed throughout the Democratic Republic of Congo (DCR) at an estimated prevalence of 0.8%. Both species, P. ovale wallikeri and P. ovale curtisi, were identified as occurring throughout the DRC.